Being Away from Home in Australia: The Indonesian Diaspora in Canberra - Wasisto Raharjo Jati (Humaniora, 2021)
The study of diasporas has been given relatively little attention by Indonesian scholars. A likely reason is the high cost of funding diaspora research in the host countries, motivating scholars to instead focus on other, less resource-intensive topics. Although the significance of this research on the Indonesian diaspora may not be immediately evident, its importance lies in how Indonesians maintain their nationalism when living overseas. Two problems particularly felt by them are homesickness and anxiety. Using an ethnographic approach, this research therefore sought to highlight how the Indonesian diaspora based in Canberra, Australia, make social bonds with each other. These bonds serve to make Canberra a second home for Indonesians, especially students and their families, permanent residents, and even naturalised citizens who have Indonesian backgrounds. A main finding was that there are various senses of Indonesianess between groups in the Canberra-based diaspora. While students are much more likely to maintain a feeling of nationalism due to scholarship policies, other groups in the diaspora, such as permanent residents and naturalised citizens, appear to hold onto their Indonesianess less tightly. Although they still engage with Indonesia, they view the country more critically, including on sensitive issues that are labelled as taboo in Indonesia. Despite the existence of these two different conceptions of Indonesianess, Canberra is their home away from home in Australia. These results consequently aid in our understanding of the significance of family ties to shaping most Asian diaspora communities living abroad.